How Many Authors Does Finland have? The Frankfurt Book Fair as a Platform for the Export of Literature and Culture - Körkkö, Helmi-Nelli (Imaginations)

(untitled) (York University, 2020)
The Frankfurt Book Fair is the world’s largest literature and media event. Every year the book fair offers an internationally recognized platform to a guest country in order to present its literature and culture. Finland was the Guest of Honour in 2014. In this article, I examine Finland’s presentation to discover what kind of platform the Frankfurt Book Fair is and what the Guest of Honour status provides for countries exporting literature and culture. This article assesses the means by which Finnish literature is exported, which authors managed to catch the attention of German media, and what the overall impact of the presentation was.